Metformin delays the decline in thermogenic function of brown adipose tissue in a mouse model of Hutchinson-Gilford progeria syndrome - Xin Xiang; Yuyue Feng; Hongcheng Li; Wenbo Li; Jia Li; Zhu Xia; Hua Pang; Zhengjie Wang (Experimental Gerontology)
Brown adipose tissue (BAT) is the primary site for non-shivering thermogenesis in the body and plays a crucial role in maintaining core body temperature. However, its function gradually declines with age. To mitigate the age-related decline in BAT thermogenic capacity, we treated progeroid mice with metformin to investigate the potential mechanisms by which metformin can slow the reduction in BAT thermogenic function. We found that progeroid mice, after receiving metformin treatment, showed significant improvement in the senescent state of brown adipocytes through the activation of SIRT1, and effectively reduced mitochondrial oxidative stress. Additionally, metformin slowed the age-related decline in UCP1 expression levels in brown adipose tissue, thereby maintaining the thermogenic capacity of the progeroid mice. Moreover, metformin reduced inflammatory responses around senescent cells, further improving the overall senescent state of the tissue. These findings suggest that metformin can slow down the aging process in brown adipose tissue by targeting SIRT1, thereby enhancing its thermogenic capacity.